Pengembangan Modul Pembelajaran Akidah Kelas X di Madrasah Aliyah - Joko Susilo; Abas Mansur Tamam; Akhmad Alim (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The purpose of this article is to comprehend the teaching of Islamic creed and its development especially in Islamic Senior High school (Madrasah Aliyah). By doing comparative study on the teaching of Tauhid and Aqedah of Ahlussunnah wal jamaah in connection with Wahhabism, the writer tries to find the middle ground as moderate Islamic understanding in reference to the book of tauhid “Qathrul Ghaib “ by Naser bin Muhammad As Samarqandi Muhammad Nawawi bin Umar Al-Jawi and the book of Aqedah by Abdul Aziz Bin M. Alu Abdul Lathif as the source material with expectation of making moderate teaching of Islamic creed module for first the grade senior high school. This module is expected to be the reference to standardized practical Islamic understanding mainly about 6 pillars of Islamic faith, to be accepted by all group of people and to accommodate the needed of basic Islamic knowledge. Its simplicity and deep explanation about 6 pillars of Islamic faith make us as readers not only believe in it and but also reflected in our deeds.